Standard Of Living In The European Union - Wawrzyniak, Dorota (Comparative Economic Research. Central and Eastern Europe, 2016)
The European Union countries are diversified in terms of the standard of living of the population. The reduction of disparities in the standard of living, along with the elimination of the negative phenomena related to social exclusion form an EU policy priority. In this context, the aim of this article is to compare the standard of living in the various European Union countries and to determine Poland’s position in the ranking. In the study, countries with a similar standard of living of their populations were grouped as well. The analysis was based on 10 variables describing the standard of living in the EU-28 countries and was conducted with the use of the development pattern method proposed by Z. Hellwig. According to the results of the research, the standard of living is the highest in Austria, Finland, Germany and Sweden, whereas it is the lowest in Spain, Malta, Croatia and Romania. Poland ranks relatively low among the European Union countries (20th place).